ANALYSIS OF MOTIVATION IN THE NOVEL CINTAMU SELUAS SAMUDERA BY GOLA GONG AND ITS IMPLICATIONS FOR LEARNING INDONESIAN LANGUAGE IN SMA - Ila Lovita, Sri Rahayu Dwiastuti, Tri Mahajani (Universitas Pakuan, 2023)
Motivation arises when there is encouragement from within and outside a person so that there is a change in attitude to do something that is desired or desired. Motivation itself can be channeled through a literary work. This study aims to Analysis Of Motivation in the novel Love As Wide As The Ocean By Gola Gong And Its Implications For Learning Indonesia In High School. The method used in this research is descriptive qualitative method, meaning that the data found are in the form of words and the results will be presented descriptively. The data used in this study are excerpts from the novel entitled Cintamu Seluas Â Samudra by Gola Gong. The data source used in this paper is the primary data source in the form of text from the novel entitled Cintamu Seluas Â Samudra by Gola Gong which was published by the publisher in 2008. The technique of collecting data in this study was a note-taking technique. Checking the validity of the data in this study using the triangulation method. The analysis of motivation which is the focus of the research is internal and external motivation. Which includes internal motivation, namely self-esteem and achievement, expectations and needs, while motivation external, namely the environmental situation in general. From the results of the study, it was found that there were 57 data findings. By looking at the analysis of the motivational aspect, it can be seen that the motivation of hope is the most common finding in this analysis, while the other three forms of motivational aspects are found to be varied in data. These results provide a positive thing for learning Indonesian in high school.